2022
DOI: 10.18820/2519593x/pie.v40.i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perceptions of the factors influencing rural school Grade 12 Business Studies learner performance in the National Senior Certificate

Abstract: The purpose of this study is to examine teachers’ perceptions of teacher factors affecting the dwindling Grade 12 learners’ performance in Business Studies National Senior Certificate (NSC) examinations at the rural Umbumbulu circuit of Umlazi district, in the province of KwaZulu-Natal, South Africa. The study employed a qualitative research methodology to explore teachers’ perceptions. Five Grade 12 teachers were purposively selected from five rural secondary schools that offered Business Studies as a subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…The findings revealed that most teachers who participated in the study understood and implemented learner-centred pedagogy in their classrooms. This finding is contrary to the finding of the study that was conducted by Mtshali et al (2022), which found that business studies teachers implement teaching approaches that do not promote learner-centredness. Most teachers who participated in the current study adopted teaching methods that promoted learner involvement in their classrooms.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings revealed that most teachers who participated in the study understood and implemented learner-centred pedagogy in their classrooms. This finding is contrary to the finding of the study that was conducted by Mtshali et al (2022), which found that business studies teachers implement teaching approaches that do not promote learner-centredness. Most teachers who participated in the current study adopted teaching methods that promoted learner involvement in their classrooms.…”
Section: Discussioncontrasting
confidence: 99%
“…One would, therefore, expect business studies learners who graduate from South African secondary schools to easily adapt to the current business environment because of the supposedly responsive business studies curriculum taught in schools, but this is not the case in many instances. Scholars suggest that the teaching methods that are adopted by teachers to teach business studies do not create a learning environment that allows learners to acquire the necessary skills (Khoza, 2019;Mtshali et al, 2022;Pihie & Sani, 2009). This is despite the common notion among scholars that learner-centred pedagogy plays an important role in facilitating learning that enables learners to acquire such skills (Ho & Dimmock, 2022;Majola, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, it is believed that Business Studies teachers were found incompetent in delivering content effectively (Mtshali et al, 2022), affecting pre-service teachers under their supervision while on TP. According to Akerman (2012), high school learners who take BS complained of being loaded with too much homework and projects and that BS is comprehensive in content.…”
Section: Literature Reviewmentioning
confidence: 99%